Meat quality parameters of five muscles of Holando steers during postmortem ageing: III. Sensorial quality - Franco, J.; Feed, O.; Bianchi, G.; Garibotto, G.; Ballesteros, F.; Nan, F.; Percovich, M.; Piriz, M.; Bentancur, O. (Agrociencia Uruguay, 2008)
The objective of this research was to study the effect of muscle type: Psoas (PS), Longissimus dorsi (LD), Semimembranosus (SM), Semitendinosus (ST) and Gluteo biceps (GB) and ageing time (1, 7, 14 and 21 days) on sensory meat quality of Holando steers Consumers detected differences in tenderness due to muscle type (P ≤ 0.001) and ageing time (P≤ 0.001). Muscle ranking was similar for all tested sensorial attributes (tenderness, flavor quality and acceptability): PS > LD > ST > SM > GB, improving the sensory ratings as the ageing period increased (21 days >14 days =7 days > 1 day). Interaction between muscle type and ageing time was highly significant (p ≤ 0.001) for all meat attributes evaluated by the consumer panel. ST and GB muscles needed longer ageing periods to improve tenderness ratings (4.85 at day 1 vs. 5.79 at day 21, and 2.97 at day 1 vs. 3.67 at day 21, for ST and GB, respectively; P ≤ 0.0001). Tenderness ratings for LD and SM muscles increased by day 7 (5.59 at day 1 vs. 7.12 at day 7, and 3.55 at day 1 vs. 4.54 at day 7, for LD and SM, respectively; P≤ 0.0001), while PS muscle reached the highest tenderness ratings by day 1, not showing any improvement in tenderness during the aging period. In contrast, GB showed the lowest tenderness ratings, and did not show significant increases in flavor quality or acceptability during ageing. These results suggest the possibility of implementing different strategies of conservation and definitively a cost-benefit equation that will change depending on the type of cut considered.